(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2026)
This study aims to examine the role of digital literacy as a mediator in the relationship between the implementation of the Independent Curriculum, learning motivation, and student academic achievement. This study develops a structural model to explain how curriculum reform improves achievement by strengthening digital competencies. A survey method was used with purposive sampling of 124 seventh and eighth-grade students at a public junior high school in Indonesia. Data were collected using a four-point Likert-scale questionnaire and analyzed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) approach. The results indicate that implementing the Independent Curriculum has a positive and significant effect on digital literacy and academic achievement. Furthermore, digital literacy was shown to mediate the relationship between the implementation of the Independent Curriculum and learning motivation, and indirectly contributed to improved academic achievement. These findings emphasize the importance of strengthening digital literacy.